PTH-269 Protein biomarkers in the rectal mucosa: a novel test for colorectal cancer?. (22nd June 2015) - Lacy-Colson, J; Norwood, M; Murray, C; Booth, J
Abstract : Introduction: Earlier detection of colorectal cancer is a clinical priority. Currently very high numbers of patients are referred for colonoscopy under the 2 week rule system, with a pick up rate for cancer of 1:20 or less putting a major strain on endoscopy units investigating large numbers of the worried well. The aim of this study was to assess the correlation of protein biomarkers captured from the rectal mucosa with the presence or absence of colorectal cancer. Method: We conducted a case control study of 20 patients with colorectal cancer, and 20 controls. All patients had been referred to colorectal outpatients with potentially worrying symptoms; presence or absence of cancer was determined by colonoscopy or CT virtual colonoscopy. A novel sampling device, OriCol™, was employed to collect samples of rectal mucosa for biomarker analysis. The device incorporates a nitrile membrane which, following insertion into the unprepared rectum via a standard proctoscope, is inflated to make contact with the rectal mucosa for a period of 10 s. Upon deflation and retraction of the membrane, a preservation buffer is added to preserve the sample prior to analysis. Sampling can be performed in an outpatient setting in under 2 min and has been shown to be well tolerated in >2500 patients. The levels of various antibodies, haemoglobin and carcinoembryonic antigen were analysed using conventional ELISA techniques. Statistical analysis of the trial results was performed using the Wilcoxon test for non-parametric comparisons with two sided p values. The area under the receiver operating characteristic (ROC) curve for distinguishing between the two diagnostic groups, together with its confidence interval, was calculated for each biomarker. Logistic regression analyses were used to investigate the performance of different combinations of biomarkers. This study was conducted with appropriate research ethics committee approval. Results: Univariate analyses identified five candidate predictive biomarkers for colorectal cancer. All combinations of two and three predictors were investigated using logistic regression. The best performing combination of biomarkers was haemoglobin and IgA. The area under the ROC curve for this best linear combination was 0.86. Conclusion: We suggest that ELISA analysis protein biomarkers collected with the OriCol™ device offers a potentially useful and cost-effective pre-colonoscopy screening tool in patients referred under the 2 week rule criteria. Data from this pilot study suggests that a sensitivity of ≥95% can be achieved while massively reducing the number of patients requiring urgent colonoscopy to exclude a diagnosis of cancer. Disclosure of interest: J. Lacy-Colson Grant/ Research Support from: Origin Science Ltd, Consultant for: Origin Science Ltd, M. Norwood Grant/ Research Support from: Origin Science Ltd, C. Murray Consultant for: Origin Science Ltd, J. Booth Employee of: Origin Science Ltd.